Does Sequencing Matter? Regulation and Privatization in Telecommunications Reforms - Wallsten, Scott (World Bank, Washington, D.C., 2013)
The question of the most effective order of reforming state-owned enterprises has been hotly debated over the years. In the early 1990s, many western advisers encouraged Eastern European countries, and the former Soviet Union, to privatize firms quickly under the assumption that market institutions would develop once firms were privately owned. The thinking since then has emphasized the importance of establishing an institutional framework conducive to promoting competition before privatizing firms. To date, there has been little empirical work clarifying the debate. The author attempts to address this gap, by examining the effects of the sequence of reform in telecommunications, particularly the effects of establishing a regulatory authority, prior to privatizing incumbent telecommunications firms. Consistent with current thinking, the author finds that countries that established separate regulatory authorities, prior to privatization, saw increased telecommunications investment, fixed telephone penetration, and cellular penetration compared with countries that did not. Moreover, he finds that investors are willing to pay more for telecommunications firms, in countries that established a regulatory authority before privatization. This increased willingness to pay is consistent with the hypothesis that investors require a risk premium to invest, where regulatory rules remain unclear.